Analisis Perilaku Komunikasi Pengguna Media Sosial Tik Tok - Pratama, Abel Abdi Putra; Narti, Sri; Yanto, Yanto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This study aims to analyze the communication behavior of Tik Tok social media users, especially non-verbal communication behavior, especially among Communication Science students at Dehasen University Bengkulu. This research uses a qualitative approach with data collection techniques in the form of interviews and observations of active students of the Communication Science Study Program who use Tik Tok. This research uses the S-O-R theory, namely Stimulus, Organism, and Response. The results showed that Communication Science students tend to dominate non-verbal communication behavior on Tik Tok. They often access videos according to interests and trends, creating content inspired by what they watch. Although the content varies, the main trends include traveling, cooking, selling, news, vlogging, thrift clothes and family drama. Participation was dominated by female students, with varied responses after using Tik Tok, including being entertained, inspired and wanting to exist through comments. Non-verbal student communication behaviors included facial expressions and gestures, clothing, visual effects, camera movements and editing, as well as reactions and interactions with other content. Students often use their creativity to attract attention, share ideas and engage in community interaction on Tik Tok.